The Link between Economic Growth and Sustainable Energy in G7-Countries and E7-Countries: Evidence from a Dynamic Panel Threshold Model - Saqib, Najia; Mahmood, Haider; Siddiqui, Aamir Hussain; Shamim, Muhammad Asif (International Journal of Energy Economics and Policy, 2022)
The available literature on sustainable energy use and economic growth nexus yields conflicting conclusions, as the effect can be positive, negative, or insignificant. This research explores the causal link between sustainable energy use and economic growth in G7-countries (Japan, Canada, Germany, Italy, France, United Kingdom, and United States) and E7-countries (Russia, Brazil, Indonesia, China, Mexico, India, and Turkey) countries from 1990 to 2019. We discover that sustainable energy use and economic growth are proportional. Our results show that sustainable energy use positively affects economic growth if E7-countries exceed a specific threshold. It is detrimental to economic growth for the E7 countries’ sustainable energy use to fall below a certain threshold. The use of sustainable energy has no significant impact on economic growth, although it does have a positive and noticeable impact in the G7 countries. In order for the countries of the G7 to see positive economic growth as a result of their investment in renewable energy, it is necessary for those nations to surpass a certain threshold in terms of their use of sustainable energy.